Is Perineural Invasio (PN) a Determinant of Disease Free Survival in Early Stage Colorectal Cancer? - ÇELİKEL, ÇİĞDEM; BOZKURTLAR, EMİNE; DANE, FAYSAL; YUMUK, PERRAN FULDEN (H G E UPDATE MEDICAL PUBLISHING S A, 2015)
Background/Aims: The prognostic importance of perineural invasion (PN) in colorectal cancer (CRC) is unclear. The aim of this study to find out whether the PN was an independent stratification factor of postoperative relapse in curatively resected high-risk stage II & III CRC patients who were treated with adjuvant therapy. Methodology: Data of patients with high risk stage II & all stage III CRCs treated with adjuvant chemotherapy were retrospectively analyzed. Pathological features of final surgical specimen were noted. Disease-free survival was determined by Kaplan-Meier estimator, with differences determined by multivariate analysis using the Cox multiple hazards model. Results were compared using the log-ranktest. Results: PN was found to be positive in 26% in the files of 593 eligible patients. In 21% of the reports PN status was not reported. Presence of PN in the resected primary tumors did not have independent effect on DFS. Further analyses for importance of PN on DFS of colon or rectal cancers did not show any effect. Conclusions: This study had failed to demonstrate any prognostic effect of PN for DFS in surgically resected stage II and III CRC patients who received adjuvant treatments.
Keywords: Perineural invasion; Colorectal cancer; Adjuvant; Survival; Prognosis; PROGNOSTIC-SIGNIFICANCE; CURATIVE RESECTION; NEURAL INVASION; RISK; RADIOTHERAPY; RECURRENCE; CARCINOMA; RELAPSE; COLON